The B-Subdomain of the Xenopus laevis XFIN KRAB-AB Domain Is Responsible for Its Weaker Transcriptional Repressor Activity Compared to Human ZNF10/Kox1 - Born, Nadine; Thiesen, Hans-Jürgen; Lorenz, Peter (PLOS ONE, 2014)
The Krüppel-associated box (KRAB) domain interacts with the nuclear hub protein TRIM28 to initiate or mediate chromatin-dependent processes like transcriptional repression, imprinting or suppression of endogenous retroviruses. The prototype KRAB domain initially identified in ZNF10/KOX1 encompasses two subdomains A and B that are found in hundreds of zinc finger transcription factors studied in human and murine genomes. Here we demonstrate for the first time transcriptional repressor activity of an amphibian KRAB domain. After sequence correction, the updated KRAB-AB domain of zinc finger protein XFIN from the frog Xenopus laevis was found to confer transcriptional repression in reporter assays in Xenopus laevis A6 kidney cells as well as in human HeLa, but not in the minnow Pimephales promelas fish cell line EPC. Binding of the XFIN KRAB-AB domain to human TRIM28 was demonstrated in a classical co-immunoprecipitation approach and visualized in a single-cell compartmentalization assay. XFIN-AB displayed reduced potency in repression as well as lower strength of interaction with TRIM28 compared to ZNF10 KRAB-AB. KRAB-B subdomain swapping between the two KRAB domains indicated that it was mainly the KRAB-B subdomain of XFIN that was responsible for its lower capacity in repression and binding to human TRIM28. In EPC fish cells, ZNF10 and XFIN KRAB repressor activity could be partially restored to low levels by adding exogenous human TRIM28. In contrast to XFIN, we did not find any transcriptional repression activity for the KRAB-like domain of human PRDM9 in HeLa cells. PRDM9 is thought to harbor an evolutionary older domain related to KRAB whose homologs even occur in invertebrates. Our results support the notion that functional bona fide KRAB domains which confer transcriptional repression and interact with TRIM28 most likely co-evolved together with TRIM28 at the beginning of tetrapode evolution.